Does cannabis use moderate smoking cessation outcomes in treatment‐seeking tobacco smokers? Analysis from a large multi‐center trial. Issue 4 (17th May 2016) - Rabin, Rachel A.; Ashare, Rebecca L.; Schnoll, Robert A.; Cinciripini, Paul M.; Hawk, Larry W.; Lerman, Caryn; Tyndale, Rachel F.; George, Tony P.
Abstract : Background and Objective: Tobacco and cannabis are frequently used in combination and cannabis co‐use may lead to poor tobacco cessation outcomes. Therefore, it is important to explore if cannabis co‐use is associated with a reduced likelihood of achieving successful tobacco abstinence among treatment‐seeking tobacco smokers. The present study examined whether current cannabis use moderated tobacco cessation outcomes after 12 weeks of pharmacological treatment (varenicline vs. nicotine patch vs. placebo) with adjunctive behavioral counseling. Methods: Treatment‐seeking tobacco smokers ( N = 1, 246) were enrolled in an intent‐to‐treat study, of which 220 were current cannabis users. Individuals were randomly assigned to 12 weeks of placebo (placebo pill plus placebo patch), nicotine patch (active patch plus placebo pill), or varenicline (active pill plus placebo patch), plus behavioral counseling. The primary endpoint was biochemically verified 7‐day point prevalence abstinence at the end of treatment. Results: Controlling for rate of nicotine metabolism, treatment arm, age, sex, alcohol, and level of nicotine dependence, cannabis users were as successful at achieving biochemically verified 7‐day point prevalence abstinence compared to tobacco‐only smokers. Conclusions and Scientific Significance: Findings suggest that cannabis use does not hinder the ability to quit tobacco smoking. Future tobacco cessation studies should employ prospective, longitudinal designs investigating cannabis co‐use over time and at different severity levels. (Am J Addict 2016;25:291–296)